Training Induced Changes to Skeletal Muscle Passive Properties Are Evident in Both Single Fibers and Fiber Bundles in the Rat Hindlimb - Noonan, Alex M.; Mashouri, Parastoo; Chen, Jackey; Power, Geoffrey A.; Brown, Stephen H. M. (Frontiers in Physiology, 2020)
Introduction: The passive mechanical behavior of skeletal muscle represents both important and generally underappreciated biomechanical properties with little attention paid to their trainability. These experiments were designed to gain insight into the trainability of muscle passive mechanical properties in both single fibers and fiber bundles. Methods: Rats were trained in two groups: 4 weeks of either uphill (UH) or downhill (DH) treadmill running; with a third group as sedentary control. After sacrifice, the soleus (SOL), extensor digitorum longus (EDL), and vastus intermedius (VI) were harvested. One hundred seventy-nine bundles and 185 fibers were tested and analyzed using a cumulative stretch-relaxation protocol to determine the passive stress and elastic modulus. Titin isoform expression was analyzed using sodium dodecyl sulfate vertical agarose gel electrophoresis (SDS-VAGE). Results: Single fibers: passive modulus and stress were greater for the EDL at sarcomere lengths (SLs) ≥ 3.7 μm (modulus) and 4.0 μm (stress) with DH training compared to UH training and lesser for the SOL (SLs ≥ 3.3 μm) with DH training compared with control; there was no effect of UH training. Vastus intermedius was not affected by either training protocol. Fiber bundles: passive modulus and stress were greater for the EDL at SLs ≥ 2.5 μm (modulus) and 3.3 μm (stress) in the DH training group as compared with control, while no affects were observed in either the SOL or VI for either training group. No effects on titin isoform size were detected with training. Conclusion: This study demonstrated that a trainability of passive muscle properties at both the single fiber and fiber bundle levels was not accompanied by any detectable changes to titin isoform size.